2023
DOI: 10.3390/ijms242115658
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of UBE2C and PLK1 Reduce Cell Proliferation and Arrest Cell Cycle by Affecting ACLY in Pan-Cancer

Keying Liang,
Qian Wang,
Li Qiu
et al.

Abstract: Various studies have shown that the cell-cycle-related regulatory proteins UBE2C, PLK1, and BIRC5 promote cell proliferation and migration in different types of cancer. However, there is a lack of in-depth and systematic research on the mechanism of these three as therapeutic targets. In this study, we found a positive correlation between the expression of UBE2C and PLK1/BIRC5 in the Cancer Genome Atlas (TCGA) database, revealing a potential combination therapy candidate for pan-cancer. Quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(122 reference statements)
0
0
0
Order By: Relevance
“…Additionally, PLK1 is indispensable for re-entering mitosis following recovery from G2 phase arrest induced by DNA damage, justifying its exploration as a potential therapeutic target for cancer [54]. Our previous studies have demonstrated that inhibiting PLK1 significantly impedes the cell cycle and proliferation of liver cancer cells [55]. Volasertib, among several PLK1 inhibitors, stands out as a highly selective inhibitor of the PLK family with the most significant effect on PLK1 [56].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PLK1 is indispensable for re-entering mitosis following recovery from G2 phase arrest induced by DNA damage, justifying its exploration as a potential therapeutic target for cancer [54]. Our previous studies have demonstrated that inhibiting PLK1 significantly impedes the cell cycle and proliferation of liver cancer cells [55]. Volasertib, among several PLK1 inhibitors, stands out as a highly selective inhibitor of the PLK family with the most significant effect on PLK1 [56].…”
Section: Discussionmentioning
confidence: 99%
“…Another paper published by Keying Liang and colleagues proposed a novel combined targeted therapy for cancer patients with higher expression levels of polo-like kinase 1 (PLK1) and ATP citrate synthase (ACLY) [11]. By using RNA-seq technology, the authors verified that the combined inhibition of ubiquitin conjugating enzyme E2 C (UBE2C) and PLK1 reduced cancer cell proliferation, migration, and colony formation, while inducing cell cycle arrest and apoptosis.…”
mentioning
confidence: 99%